Molecular Docking in red spinach plants (Amaranthus tricolor L.) as an inhibitory agent for genetic anemia - Fattara, Fajar Putra; Idami, Zahratul; Silalahi, Ali Affan (Institute of Computer Science (IOCS), 2024)
This study aims to evaluate the potential of active compounds from the Red Spinach plant (Amaranthus tricolor L.) as an inhibitor agent for the genetic disease anemia through a molecular docking approach. The method used involved analyzing the 3D structures of four active compounds Phenol, Lutein, Quercetin, and Zeaxanthin in these plants, which were downloaded from PubChem and processed using the Swiss software Target Prediction, Super Prediction, PyMol, and PyRx. The interaction between the compound and the biological target, in this case, Erythropoietin, is evaluated to determine binding energy, binding affinity, and stability. The results showed that Phenol and Quercetin had a significant interaction with the lowest binding energy of -4.8 kcal/mol and -8.1 kcal/mol respectively, as well as the lowest RMSD value (0 Å), indicating good interaction stability with the protein target. The 3D molecular structure of these two compounds also indicates the presence of hydrogen bonds and effective interactions with amino acids, as well as low toxicity and favorable affinity energies. Based on these results, Phenol and Quercetin were identified as potential candidates in the development of drugs to treat anemia genetic diseases, thanks to their favorable interaction properties and molecular structural characteristics. This research underlines the importance of the molecular docking approach in identifying bioactive compounds that can be further developed as therapies for the genetic disease anemia.